Demonstration and Characterization of a Persistent Pheromone Lure for the Navel Orangeworm, Amyelois transitella (Lepidoptera: Pyralidae) - Bradley S. Higbee; Charles S. Burks; Thomas E. Larsen (Insects, 2014)
The lack of an effective pheromone lure has made it difficult to monitor and manage the navel orangeworm, Amyelois transitella (Lepidoptera: Pyralidae), in the economically important crops in which it is the primary insect pest. A series of experiments was conducted to demonstrate and characterize a practical synthetic pheromone lure for capturing navel orangeworm males. Traps baited with lures prepared with 1 or 2 mg of a three- or four-component formulation captured similar numbers of males. The fluctuation over time in the number of males captured in traps baited with the pheromone lure correlated significantly with males captured in female-baited traps. Traps baited with the pheromone lure usually did not capture as many males as traps baited with unmated females, and the ratio of males trapped with pheromone to males trapped with females varied between crops and with abundance. The pheromone lure described improves the ability of pest managers to detect and monitor navel orangeworm efficiently and may improve management and decrease insecticide treatments applied as a precaution against damage. Awareness of differences between male interaction with the pheromone lure and calling females, as shown in these data, will be important as further studies and experience determine how best to use this lure for pest management.